Experimental Verification of Impact of Sprinkled Area Length on Heat Exchange Coefficient - Petr Kracik; Marek Balas; Martin Lisy; Jiri Pospisil (Advances in Materials Science and Engineering)
On a sprinkled tube bundle, liquid forms a thin liquid film, and, in the case of boiling liquid, the liquid phase can be quickly and efficiently separated from the gas phase. There are several effects on the ideal flow mode and the heat transfer from the heating to the sprinkling liquid. The basic quantity is the flow rate of the sprinkling liquid, but also diameter of the tubes, pipe spacing of the tube bundle, and physical state of the sprinkling and heating fluid. Sprinkled heat exchangers are not a new technology and studies have been carried out all over the world. However, experiments (tests) have always been performed under strict laboratory conditions on one to three relatively short tubes and behaviour of the flowing fluid on a real tube bundle has not been taken into account, which is the primary aim of our research. In deriving and comparing the results among the studies, the mass flow rate based on the length of the sprinkled area is used, thus trying to adjust the different length of the heat exchanger. This paper presents results of atmospheric pressure experiments measured on two devices with different lengths of the sprinkled area but with the same number of tubes in the bundle with same pitch and surface at a temperature gradient of 15/40°C, where 15°C is the sprinkling water temperature at the outlet of the distribution pipe and 40°C is the temperature of heating water entering the bundle.